Polyoxometalate Composites in Cancer Therapy and Diagnostics. Issue 22 (30th April 2020) - Guedes, Gabriela; Wang, Shiqi; Santos, Hélder A.; Sousa, Filipa L.
Abstract : Polyoxometalates (POMs) are metal‐oxide inorganic clusters, mostly anionic, where the metal is usually a transition metal (such as V, W, or Mo). Owing to their great variety of structures and large range of molecular dimensions, POMs have attracted considerable attention over the years. The high solubility in water together with the extent of their redox chemistry make POMs and their composites very versatile materials that find many applications in the biomedical field such as drug delivery systems or anti‐viral and anti‐tumoural agents. While the antitumoural activity of POMs and their derivatives is well documented, their application in emergent cancer therapies has not been addressed. This review presents the application of POM‐based composites as photothermal agents, radiosensitisers, and biosensors. The latest advances in the design of novel POM nanocomposites for cancer theranostics are also highlighted. Abstract : A new role: Beyond the classic antitumoural activity of polyoxometalates, their emergent role in radiotherapy and photothermal therapy is expected to impact the research devoted to cancer therapy. This Minireview covers the application of POM‐based composites as photothermal agents, radiosensitizers, biosensors, and the latest advances in the development POM theranostic systems.